STUDY OF THE ELDERLY DEMENTIA IN PANTI WREDHA DARMA BAKTI SURAKARTA - Untari, Ida (JURNAL PROFESI || MEDIA PUBLIKASI PENELITIAN, 2014)
The increasing life expectancy of the population in Indonesia, causing the number of elderly people is increasing from year to year. The prediction results showed that the percentage of the elderly population will reach 9.77 percent of the total population in 2010 and to 11.34 percent in 2020. The problems that often arise in the elderly one of them a form of intellectual cognitive disorder or senile dementia. Dementia is a clinical syndrome that includes loss of intellectual function and memory so serious that it causes dysfunction of everyday life. The purpose of this study to know the changes in memory elderly in Panti Wreda Darma Bakti Surakarta. This study used a descriptive method with cross sectional approach. The population in this study a total of 90 elderly. Sampling based on inclusion and exclusion criteria, the number of respondents 60 elderly. The sampling technique used purposive sampling. The research instrument using the Short Portable Mental Status Questionnaire (SPMSQ) to measure dementia. Analysis of the data using univariate analysis. The results showed most respondents in the older group (54-65 years) is10 persons (16.7%), and 50 elderly people at risk (83.35). Elderly with mild dementia 11 persons (18.3%), dementia was 21 persons (35%) and severe dementia 28 persons (46.7%). The conclusions in this study, elderly in nursing homes Darma Bakti Surakarta majority including the elderly at risk and most experienced dementia (memory loss) in severe. Â  Keywords: Dementia, Elderly